Single mothers: their health and health service use. Issue 4 (December 1989) - Beatson-Hird, P; Yuen, P; Balarajan, R
Abstract : STUDY OBJECTIVE: The aim of the study was to investigate differences in reported health and health service use in single mothers. DESIGN: The study was a survey of data derived from the General Household Surveys conducted by the Office of Population Censuses and Surveys (OPCS). SETTING: The OPCS data are derived from samples of households throughout Great Britain. PARTICIPANTS: OPCS data for 1983 and 1984 were used, comprising approximately 60, 000 individuals, of whom 793 were single mothers. MEASUREMENTS AND MAIN RESULTS: Five different health outcomes were examined, two on perceived morbidity and three on the use of health services. The chief determinants of health and health services use among single mothers were housing tenure, employment status and the age of the youngest child. Single mother status did not consistently contribute to self reported morbidity and uptake of care when adjusted for other social variables, but there was a difference between categories of single mother, with those who were separated/divorced and those who were widowed reporting more acute illness than those who were married. CONCLUSION: The findings suggest that single mothers do not form a homogeneous group and that, if special consideration is to be given to them when planning and allocating health service resources, this needs to be taken into account in the context of other socioeconomic factors.